Equality in matters of the heart?. Issue 1 (5th July 2021) - Balan, Prakash; Eng, Marvin H.
Key Points: Gender‐based differences in TAVR outcomes remains significant. Gender‐based differences in TAVR outcomes persist despite technological advancements reducing catheter profiles and inclusion of lower surgical risk patients. Further study aimed at controlling for differences in anatomical dimensions may improve our understanding of the gender gap in TAVR.